Compositional analysis of fatty acids in cow’s milk when feeding a complex additive based on activated diatomite - Akhmetova Venera (EDP Sciences, 2021)
The article presents the research results of the effect of activated diatomite as part of a complex supplement on the composition and ratio of saturated and unsaturated fatty acids in cow's milk. The experiments were carried out in a dairy farm on black-and-white cows. The additive includes a carrieractivated diatomite; fillers are DAPS-organic selenium, sunflower oil and feed yeast and diatomite crumbs. The supplement was included in the diet of cows at the rate of 2% of the dry matter of the diet once a day. The control group did not receive the supplement. The positive effect of the use of the additive on the composition of fatty acids in cow's milk was established. There was an increase in the fraction of saturated fatty acids, which indicates an increase in volatile fatty acids: acetate and 3-hydroxybutyrate. The use of a complex supplement based on activated diatomite contributed to an increase in concentration of capric, lauric, myristic, palmitic and margarine fatty acids. The use of additives for dairy cows helps to increase their productivity, improve the quality of milk composition due to the intensive conversion of feed nutrients.